Zygmunt Bauman : Why Good People do Bad Things. - Best, Shaun (Public intellectuals and the sociology of knowledge., 2016)
In this ground-breaking book, Shaun Best analyses the intellectual knowledge production of Zygmunt Bauman and his rise to academic stardom in the English speaking world by evaluating the relation between his biography, the contexts in which he found himself, and why his intellectual creativity is admired by so many people. Bauman has an interesting 'contested' biography and underwent a number of intellectual shifts from the early stages of his academic career as Marxist. Bauman moved on and for almost ten years he was associated with 'postmodernity' (from 1989-1997) but in 2000 he decided to distance himself from postmodernism and rebrand his approach to understanding the contemporary world as 'liquid modernity'. Best shows how Bauman developed his canonised status becoming an intellectual guru in the UK and in Australia despite being largely ignored by the academic community in the United States and Central Europe. Rather than investigating Bauman's academic output as a demonstration of his 'creative genius', Best argues that most academic output involves the interplay of multiple factors and this book evaluates the influences on both intellectual choices and the social factors or contexts that led Bauman to attach himself to different sets of ideas during his academic career.